Plan pour l'éducation d'un jeune seigneur russe: manuscrito de Ribeiro Sanches (1766): leitura, transcrição, tradução e comentários filológicos - Brian F. Head (Documentos, 2016)
The present study constitutes the first diplomatic edition of the text in which the doctor, philosopher and educator António Ribeiro Sanches proposes a plan for the education of the young Russian noblemen (manuscript of 1766). After studying with the famous Dutch physician and chemist Hermann Boerhaave, the propagation of whose methods he promoted notably (in the Universities of Coimbra, Strasburg and Saint Petersburg), Ribeiro Sanches spent sixteen years in Russia providing scientific and professional services with official status. The plan for the education of the young Russian noblemen was written at the request of the illuminated Empress Catherine II, as part of the cultured and political openness that the promoted. In the proposal of Ribeiro Sanches, one notes properties that are innovative and modern for the time, such as the practical nature of the proposed instruction, as well as its usefulness, social tolerance and scientific and organizational rigor.